2014
DOI: 10.1186/2041-1480-5-2
|View full text |Cite
|
Sign up to set email alerts
|

The languages of health in general practice electronic patient records: a Zipf’s law analysis

Abstract: BackgroundNatural human languages show a power law behaviour in which word frequency (in any large enough corpus) is inversely proportional to word rank - Zipf’s law. We have therefore asked whether similar power law behaviours could be seen in data from electronic patient records.ResultsIn order to examine this question, anonymised data were obtained from all general practices in Salford covering a seven year period and captured in the form of Read codes. It was found that data for patient diagnoses and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 22 publications
(22 reference statements)
1
9
0
Order By: Relevance
“…This was less skewed than typical 80/20 Pareto distributions, which may highlight the interchangeable use of terms. The low type–token ratio in this study suggested an appropriate sample for language analysis . Similar data sets from electronic health records used by general practitioners in England have viewed terms as a language distribution .…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…This was less skewed than typical 80/20 Pareto distributions, which may highlight the interchangeable use of terms. The low type–token ratio in this study suggested an appropriate sample for language analysis . Similar data sets from electronic health records used by general practitioners in England have viewed terms as a language distribution .…”
Section: Discussionmentioning
confidence: 75%
“…The low type–token ratio in this study suggested an appropriate sample for language analysis . Similar data sets from electronic health records used by general practitioners in England have viewed terms as a language distribution . Language distributions can assist in selecting paediatric terms to develop standard paediatric terminology when used in combination with an age definition.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations